Expression for a general element of an SO(n) matrix - T. M. Janaki; Govindan Rangarajan (International Journal of Mathematics and Mathematical Sciences)
We derive the expression for a general element of an SO(n) matrix. All elements are obtained from a single element of the matrix. This has applications in recently developed methods for computing Lyapunov exponents.